Aqidah Akhlak Contributors People Voice and Builders Akhlakulkarimah - M Zainul Umam (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2022)
The implementation of aqidah akhlak education can be seen as a forum to foster and shape the behavior of students in developing knowledge (cognitive), attitude (affective) and habituation (psychomotor). Aqidah akhlak education should push all these aspects towards achieving the perfection of life based on Islamic values. The formation of karimah character among madrasah aliyah students through the learning of aqidah akhlak. The purpose of aqidah akhlak education is to instill and improve the faith of students and raise awareness to akhlakulkarimah. Learning activities are an effort to create a pedagogical and anthrogic atmosphere that is conducive to the situation and conditions to achieve a more effective, efficient and enjoyable standard of moral competence. The influence of aqidah akhlak education in life and bring changes to the behavior of students who are better and responsible, especially in the implementation of Islamic teachings in everyday life. A teacher is expected to master learning methods that can encourage students to be active in the classroom. The lecture method is very important, but if it is not balanced with other methods or strategies it will become very boring. The inhibition factor in the formation of akhlakulkarimah character, especially through the learning of aqidah akhlak in madrasah aliyah is: the basic ability of the students who follow the lessons of moral aqidah is very diverse. The lack of attention of students to moral problems, learning materials aqidah akhlak emphasize more cognitive aspects, control of students outside the lesson is quite difficult.